1991
DOI: 10.1111/j.1600-0536.1991.tb01879.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis caused by allergy to ophthalmic drugs and contact lens solutions

Abstract: Although a common cause of allergic reactions, topically applied ophthalmic drugs and contact lens solutions are seldom verified as such. This review documents reported allergens and suggests an 'ophthalmic tray', based on the literature search, to simplify patch test verification. The criteria for literature selection were that each patient had a history of allergic reaction to local application of ophthalmic drugs or contact lens solutions, and tested positive to putative allergen patch tests. We established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…31 There have been several case reports of allergy from use of local anesthesia or proparacaine eyedrops. 99,100 Although cross-sensitization between proparacaine and other related topical ophthalmologic anesthetic agents such as tetracaine is a rare occurrence, some studies 100 suggest that allergic sensitization and possible cross reaction to topical anesthetic agents in ophthalmologists is an occupational hazard.…”
Section: Allergymentioning
confidence: 99%
“…31 There have been several case reports of allergy from use of local anesthesia or proparacaine eyedrops. 99,100 Although cross-sensitization between proparacaine and other related topical ophthalmologic anesthetic agents such as tetracaine is a rare occurrence, some studies 100 suggest that allergic sensitization and possible cross reaction to topical anesthetic agents in ophthalmologists is an occupational hazard.…”
Section: Allergymentioning
confidence: 99%
“…Benzalkonium chloride has been classified as a rare sensitizer, 6 but this classification has been challenged by suggestions that it may not be a sensitizer because of its strong irritant property complicating the differentiation of irritant from allergic patch test results. 4 Nevertheless, many case studies have reported sensitization to BAK as a result of occupational exposure 7 as well as with exposure to detergents/antiseptics, 7Y11 antifungal treatments, 12 ophthalmic preparations, 9,13,14 toothpastes, 15 and plaster of paris. 16,17 A review by Herbst and Maibach 14 of reported cases of contact allergy suspected from ophthalmic preparations yielded 16 cases of positive patch tests to BAK, which utilized concentrations ranging from 0.005% to 0.13% aq.…”
mentioning
confidence: 98%
“…The reported cases were caused or triggered by thimerosal in ophthalmic preparations and cleansing solutions for contact lenses (de Groot et al 1990, Herbst and Maibach 1991, Ortiz et al 1991, Tosti and Tosti 1988, Whittington 1985 or other preparations (e.g. Chastagner et al 1988, Landa et al 1990.…”
Section: Effects In Manmentioning
confidence: 99%